2016
DOI: 10.1177/1059840516649234
|View full text |Cite
|
Sign up to set email alerts
|

Health Services in Boarding School

Abstract: Adolescents who attend high school as preparatory boarding students are growing up and learning to care for themselves in a very different set of circumstances than those who live at home with their families. Although this choice may present myriad opportunities for personal growth and academic advantages, nurturance and support from caring adults is necessary to foster health and well-being. Our model of a collaborative relationship between nursing and counseling in providing health services to the adolescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Overall, higher rates of sexual intercourse, higher prevalence of smoking, and alcohol and drug consumption were reported as more prevalent among boarding students as compared to non-residents. It is possible that the greater independence and freedom experienced at this age is potentially problematic [13,39]. These data suggest that boarding students warrant greater emphasis on health risk screening and preventive counseling.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Overall, higher rates of sexual intercourse, higher prevalence of smoking, and alcohol and drug consumption were reported as more prevalent among boarding students as compared to non-residents. It is possible that the greater independence and freedom experienced at this age is potentially problematic [13,39]. These data suggest that boarding students warrant greater emphasis on health risk screening and preventive counseling.…”
Section: Discussionmentioning
confidence: 97%
“…The implication of the study findings is clear that the significant associations between boarding students and risky health behaviors should be considered in policies and guidelines. In this sense, more structured and healthy environments may be necessary for students who live at this kind of residence [13]. These students need more attention, advice, and health-promotion activities to lead them to responsibility and a conscientious use of their freedom.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, meals and health care are provided. Howewer, the quality of these services is not as good as the nutrition and health services at some schools in Shaanxi (Yue et al's, 2008) and other schools as reported by Pucher et al (2013) and Pavletic et al (2016). Further, the safety is doubting despite the use of CCTV and the presence of permanent caretakers at the dormitory area.…”
Section: Welfare Servicesmentioning
confidence: 91%